Impact of Ferroelectric Layer Thickness on Reliability of Back‐End‐of‐Line‐Compatible Hafnium Zirconium Oxide Films. Issue 4 (6th October 2022) - Sünbül, Ayse; Lehninger, David; Hoffmann, Raik; Olivo, Ricardo; Prabhu, Aditya; Schöne, Fred; Kühnel, Kati; Döllgast, Moritz; Haufe, Nora; Roy, Lisa; Kämpfe, Thomas; Seidel, Konrad; et al.
Abstract : Due to its ferroelectricity, hafnium oxide has attracted a lot of attention for ferroelectric memory devices. Amongst different dopant elements, zirconium is found to be beneficial due to the relatively low crystallization temperature of hafnium‐zirconium‐oxide (HZO), thus it is back‐end‐of‐line (BEoL) compatible. The thickness of HZO has a significant impact on ferroelectric device reliability. High operation temperatures and high endurance are important criteria depending on the application. Herein, various HZO thicknesses (7, 8, and 10 nm) in MFM (metal‐ferroelectric‐metal) capacitors are investigated at varying operation temperatures (25 to 175 °C) at varying electric fields (±3 to ±5.4 MV cm −1 ) with respect to polarization, leakage current, endurance, and retention. 7 nm HZO showed promising results with an endurance of 10 7 cycles, with a low leakage current density, and almost no retention loss after 10 years. Extrapolated results at operation conditions (±2 MV cm −1 and 10 MHz) showed an endurance of 10 10 cycles. Abstract : Back End of Line‐compatible hafnium zirconium oxide films for non‐volatile memory applications are optimized at different temperatures. 7 nm HZO showed promising results with an endurance of 10 7 cycles, with a low leakage current density, and almost no retention loss after 10 years. Extrapolated results at ±2 MV cm −1 and 10 MHz showed an endurance of 10 10 cycles.